Social representations and risks seen by central African students studying in France : Norms and Boolean - (:unkn) unknown (My University, 2020)
This research work is in line with the theory of social representations and aims to explain how Central African students studying in France construct their social representations of risks depending on whether they have a project to settle in France or intend to return to their countries of origin. Our population (N=90) is divided into two groups: the group of students who plan to settle in France (N=45) and the group of students who want to return home (N=45). The main hypothesis postulates that "Social representations of risk among students who want to stay in France differ from those of students who want to return to their countries of origin". Thanks to the data collected through the free associations and the characterization questionnaire, we find on the one hand, that the answers of students who want to stay in France emphasize the risks related to the socio-economic and security aspect in Central Africa. On the other hand, students who plan to return to their countries highlight isolation, loneliness, depression, poverty and unemployment; these are the main characteristics of risks in France. The social representations of risks of these two groups show differentiated representations in the two environments. The use of specific methodologies such as Boole's Algebra shows the importance of normative aspects and compensatory strategies in the study of social representations. This methodology confirms its relevance to cultural issues.
Keywords: African Research